Importance of local weather and environmental gradients on demography of a broadly distributed temperate frog. (March 2022) - Pilliod, David S.; McCaffery, Rebecca M.; Arkle, Robert S.; Scherer, Rick D.; Cupples, Jacqueline B.; Eby, Lisa A.; Hossack, Blake R.; Lingo, Hallie; Lohr, Kristin N.; Maxell, Bryce A.; McGuire, Megan J.; Mellison, Chad; et al.
Highlights: Population demography of the Columbia spotted frog varies with seasonal weather. Adult survival in a population is predictable along a species-environment response curve. In contrast, recruitment responds to local conditions independently at each population. Thus, climate predictions may need demographic data across environmental gradients. Local context and scale of inquiry are key to understanding climate change effects. Abstract: Amphibian populations are sensitive to environmental temperatures and moisture, which vary with local weather conditions and may reach new norms and extremes as contemporary climate change progresses. Using long-term (11–16 years) mark-recapture data from 10 populations of the Columbia spotted frog ( Rana luteiventris ) from across its U.S. range, we addressed hypotheses about how demographic relationships to weather depend upon a population's position along climate gradients. We estimated the effect of seasonal weather on annual survival probability and recruitment rates both within populations and across the species' range from subalpine forests to semi-arid deserts. We calculated population-specific weather variables that captured seasonal temperature and precipitation between summer sampling events, both for periods when frogs were active (spring to fall) and inactive (winter). Across all populations, we marked 15, 885 adult frogs, with 33% of frogs recaptured at least once. Population demography varied with seasonal weather across the species' range. Annual adult survival probability and recruitment rates of each population were influenced by a unique set of seasonal temperature and precipitation variables, particularly in winter and spring. Hence, adult survival varied with local conditions but, when analyzed across all populations, was predictable along a species-environment response curve associated with the timing of snowmelt and spring moisture. In contrast, recruitment rates for each population peaked at different values along an environmental gradient associated with the amount of snow during winter, and fall temperature and moisture levels, suggesting that recruitment may be responding to local conditions independently within each population. These findings highlight that sampling across the environmental (i.e., elevational and meteorological) gradients within a species range is necessary to predict species-level responses to regional climate change. This study also provides evidence of the importance of winter conditions on the demography of temperate amphibians, conditions that are already responding to climate change. Finally, this study further emphasizes that local context and spatiotemporal scale of inquiry remain paramount to understanding and potentially managing for climate effects on populations of amphibian species with broad geographic ranges.